Geochronological Constraints on the Tropicana Gold Deposit and Albany-Fraser Orogen, Western Australia - Doyle, M.; Fletcher, Ian; Foster, J.; Large, R.R.; Mathur, R.; McNaughton, Neal; Meffre, S.; Muhling, Janet; Phillips, D.; Rasmussen, Birger (Society of Economic Geologists Inc, 2015)
Gold mineralization at the Tropicana mine occurs within the Plumridge terrane along the eastern margin of the Archean Yilgarn craton in the Albany-Fraser orogen, Western Australia. Mineralization is hosted in a favorable syenitic lithofacies of the Tropicana Gneiss with a minimum igneous age of 2638 ± 4 Ma (2σ) and which was metamorphosed to mid-amphibolite to lower granulite facies in the period ca. 2638 to 2520 Ma. The Tropicana Gneiss was exhumed to crustal levels equivalent to greenschist-facies conditions by the time of economic gold mineralization. The major gold-bearing pyrite-biotite-sericite mineralization formed in association with shear zones during northeast-southwest compression (D3) that postdated W- to NW-verging thrusting (D2). The late fluid-induced event (Tropicana event; Doyle et al., 2013; Blenkinsop and Doyle, 2014) produced a mineral assemblage indicative of greenschist-facies conditions. The paucity of water in granulite-facies gneisses under retrograde conditions suggests that fluids were introduced from an external source for both mineralization and the younger metamorphic event. This occurred at ca. 2520 Ma as determined from biotite (ca. 2515 Ma, 40Ar/39Ar age), pyrite (ca. 2505 Ma, Re-Os, Pb/Pb ages), and tungsten-rich rutile (2521 ± 5 Ma, U-Pb age): the latter is considered to provide the best direct measurement age of gold mineralization. The Tropicana Gneiss was derived from the upthrusted easternmost margin of the underlying Yilgan craton, or represents a relatively small (160 km long × 50 km wide) remnant crustal block accreted to the Yilgarn craton sometime between ca. 2.6 and 2.5 Ga. The timing of the Tropicana mineralization is distinctly younger than greenstone-associated gold deposits elsewhere in the Yilgarn craton. As in the Dharwar craton, India, and the Limpopo belt, Zimbabwe, economic gold mineralization at Tropicana postdates the major peak of Late Archean world-class gold mineralization (ca. 2.65 Ga) by more than 100 m.y. The Tropicana Gneiss was relatively unaffected during the younger Albany-Fraser orogeny, with only minor remobilization of gold. Deformation may have been localized at the margins of the domain, between constituent ridged structural blocks, and/or within discrete high-strain shears.